Comparison of Aflatoxin B1 Measurement Efficiencies of 5 MHz QCM and 120 MHz Love Wave Sensors - Pirincci, Serife Seyda; Ertekin, Ozlem; Ozturk, Zafer Ziya; Ozturk, Selma (Int Frequency Sensor Assoc-Ifsa, 2018)
Aflatoxin B1 (AFB1), which is a prominent fungal secondary metabolite due to its hepatoxic and carcinogenic properties, is monitored due to its negative effects on health. However, since these observations are carried out with laboratory installed devices, the increase of contamination after measurement can not be observed and therefore, the contaminating products can be presented to the user. Biosensors are seen as strong candidates in order to make the monitoring more efficient and effective. There are many biosensor studies for detection of aflatoxins with biosensors, but they are not yet used in routine biosensor monitoring. The reason for this is argued as the sensitivity of these devices and measurement precision can not compete with the built-in devices. Therefore, stable and precise measurement methods and technologies need to be developed. In this study, Love wave biosensor was used for the first time for measurement of free Aflatoksin B1 and the results obtained with this study was compared with the results of 5 MHz QCM measurements. For both of these studies the same measurement method was applied. As a result of the study, it was observed that 250 ppt can be determined with a 120 MHz Love wave sensor while 5 MHz QCM can measure 1250 ppt AFB1 at a minimum.
4th International Conference on Sensors and Electronic Instrumentation Advances (SEIA) -- SEP 19-21, 2018 -- Amsterdam, NETHERLANDS
Keywords: Aflatoxin B1; QCM; Love wave; Biosensor